Linux for Dummies 6th Edition - LeBlanc, Dee-Ann (Wiley Publishing, 2011)
This book tells you how to install, configure, and customize a Linux desktop system. Although you can do most things in Linux these days by pointing and clicking, you still may want to try using Linux at the command prompt — where you type detailed instructions to load or configure software, access files, and do other tasks. In this book, input appears in monospace type